Research progress of psychological interventions for patients with diabetic foot and anxiety (糖尿病足合并焦虑患者心理干预研究进展) - HOU Xuemin (侯雪敏); HUANG Yanping (黄砚萍); WANG Ting (王婷) (Association of Integrative Nursing, 2024)
The incidence of type diabetes mellitus tends to increase with gradual aging of the population, leading to the increasing number of patients with diabetic foot ulcers. Patients may suffer from emotional disorder at any stage of disease. The emotional status is highly related to the development of diabetic foot ulcers, and has a major influence on following treatment and quality of life of patients. The current therapy model combines two evidence-based treatments: drug therapy including anxiolytics and newer antidepressants, non-drug therapy including cognitive-behavioral therapy, psychological care, music therapy and Traditional Chinese Medicine emotional nursing. This paper reviewed studies on pathogenesis, development and interventions on diabetic foot complicating anxiety disorder. (随着我国老龄化逐渐加剧, 老年2型糖尿病患者也日益增多, 同时伴随着足部溃疡的患者数量呈上升趋势。患者在疾病发生、发展的过程中均会出现不同程度的情绪障碍, 而情绪又与糖尿病足的发生、发展息息相关, 对于患者的治疗以及生存质量有着重大的影响。在治疗上主要包括药物治疗和非药物治疗两种方式, 药物治疗主要包括抗焦虑药物和新一代抗抑郁的药物; 非药物治疗主要有认知行为干预、心理护理、音乐疗法、中医情志护理的方法等。本文从糖尿病足合并焦虑的发病机制、发展原因、干预措施等方面进行综述, 并做简要分析。)